The Values of Local Wisdom in The Ngaji Rasa Sejarah Alam on Krimun Village Community Losarang District Indramayu Regency as a Source of Social Studies Learning - Rahayu, Ani (Universitas Pendidikan Indonesia, 2020)
This research is motivated by the researcher’s interest in the values of local wisdom in the ngaji rasa sejarah alam theory on Suku Dayak Hindu Budha Bumi Segandu Indramayu. It is caused by the result of the researcher’s finding that the values of local wisdom in the ngaji rasa sejarah alam theory can be used as a source of learning in social study learning. Where the use of learning resources based on the values of local wisdom in society is still rarely used by educators. The general purpose of this research is to find out the values of local wisdom that exist in the Suku Dayak Hindu Budha Bumi Segandu Indramayu, besides the specific purpose is to find out the characteristics, attempts to maintain the ngaji rasa sejarah alam Theory and identify the values of it in the Suku Dayak Hindu Budha Bumi Segandu Indramayu that can be used as a source of social study learning. In this research, researchers used a descriptive method with a qualitative approach. The results of this search indicate that (a) the characteristics of the Suku Dayak Hindu Budha Bumi Segandu Indramayu are people who wear black and white shorts, bare chests, wear necklace and 3 bracelets on their feet and hands, long-haired, adhere to the natural history theory with its traditional kum-kum, laku pepe, kliwon Friday night ritual, vegetarianism, and devotion to the wives and children. (b) values that are contained: tolerance, ecological intelligence, mutual cooperation, responsibility, and good behavior which is then implemented through the making of the lesson plan based on local wisdom.